Imām al-Ḥaramayn al-Juwaynī and Jadal Theory in the Eleventh Century (A Critical Analysis of Imām al-Ḥaramayn’s al-Kāfīya fi al-jadal) - Mohammad Syifa Amin Widigdo (P3M STAIN Kudus, 2018)
This study presents a critical navigation and interpretation of the book al-Kāfiya fī al-jadal by Imām al-Ḥaramayn al-Juwaynī (d. 478/1085). In this book, he elucidates foundational thoughts of jadal (dialectic) theory and its application. Despite its importance in the development of jadal in Islamic scholarship and dialectical art, Imām al-Ḥaramayn’s al-Kāfiya unfortunately has never been studied. Existing studies on the art of Islamic disputation theory discuss al-Kāfiya’s position and contribution, but the discussion of its content is not comprehensive. In this respect, this article not only provides a more comprehensive understanding of Imām al-Ḥaramayn’s theory of jadal but more importantly demonstrates how Imām al-Ḥaramayn formulates jadal as a scholastic method. He shows that jadal is essentially scholastic for its orientation of finding truth in the forms of epistemological and psychological certainty (al-yaqīn) in juridical and theological knowledge.